METHOTREXATE — «GOLD STANDARD» OF JUVENILE RHEUMATOID ARTHRITIS TREATMENT - Ye. I. Alekseyeva; S. I. Valiyeva; T. M. Bzarova; R. V. Denisova (Вопросы современной педиатрии, 2011)
The article presents the literature review of recent publications on efficacy and safety of methotrexate in treatment of juvenile rheumatoid arthritis. Administration of methotrexate 15 mg/m2 of body surface weekly results in significant decrease of inflammatory activity of rheumatoid process and in several cases in induction of clinical and laboratory remission of the disease. Maximal effect can be achieved via subcutaneous or intramuscular injection.